Enhancing Ecological Education in Argumentative Essay through Critical Thinking Skills - Moh. Yamin; Tri Winindyasari Palupi; Vivi Aulia (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
The issue of ecological education in argumentative essay writing with critical thinking skills is interesting to discuss. This study aimed to enhance ecological education in the argumentative essay through critical thinking to the students. The approach and method used in this study are qualitative-descriptive. The subject of the research is the students of junior high schools near river and wetlands. The instrument used is a questionnaire; the data gotten from the questionnaire is coded manually and the analysis is content analysis. The study result shows that the learners enhanced with ecological education have an awareness of their environment and they get easier to write their argumentative essay because the issue is close to them. Their linguistic competence is trained because they are able to use the vocabulary well. The learners have a wide knowledge of what to write and discuss in their writing activities. What happens in their environment becomes the material to narrate and it is the main part of ecological education contribution in their argumentative essay writing.